2020
DOI: 10.24191/abrij.v6i1.9953
|View full text |Cite
|
Sign up to set email alerts
|

Influence Cross Membership and Qualifications of The Shari’ah Supervisory Board’s Towards The Shari’ah Compliance related SSB Information

Abstract: The purpose of this paper to analyze the influence of Shari’ah Supervisory Board Cross Memberships and Shari’ah Supervisory Board Qualification toward Shari’ah compliance related SSB information. In addition, this paper also explains the variable firm size as a control variable. The use of control variables so that the influence of SSB on compliance does not depend on other variables. This study reviews the Shari’ah compliance related SSB information as stated in the Accounting and Auditing Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to (Fakhruddin et al, 2020) revealed that, educational background is a significant factor in the disclosure practice. Education can be used as a sole measure for determining the professional level.…”
Section: Sharia Scholarsmentioning
confidence: 99%
“…According to (Fakhruddin et al, 2020) revealed that, educational background is a significant factor in the disclosure practice. Education can be used as a sole measure for determining the professional level.…”
Section: Sharia Scholarsmentioning
confidence: 99%
“…It is possible to maximize the effectiveness of maqashid sharia in Islamic banking by having more talks about how Islamic law is used in carrying out its operational tasks. The results of research conducted by Agustina and Maria (2017), Nomran (2017), andFakhruddin et al (2020) Since the failure of some of the world's largest corporations, such as Enron, WorldCom, Tyco, and Parmalat due to the poor implementation of corporate governance, governments, companies, academics, and various other parties, as well as the public, have begun to realize the issue of gender diversity within the board structure (Randøy et al, 2006). The creation of GCG can be influenced by the presence of women's boards because women's boards are considered to be able to increase the monitoring and independence of the board (Maghfiroh and Utomo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By examining the role of two aspects of the sharia governance mechanism from the study, namely the variable cross-membership and the women's gender of the SSB, the research distinguished itself from several prior studies (Ramadhan et al, 2018;Agustina and Maria, 2017;Nomran, 2017;and Fakhruddin et al, 2020). Research that explores the impact of IC on the performance of sharia maqahids with cross-membership and the gender of women on SSB as moderating variables is needed because the findings of earlier studies had gaps.…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of a member of the Shariah Supervisory Board is not a reason for management to do or not do earnings management. This is possible because only about 25% of the Shariah Supervisory Board in Indonesian Islamic financial institutions have doctoral backgrounds in the fields of Islamic Law, economics, and finance and accounting, and only about 10% of the Shariah Supervisory Board has a doctorate background in economics, finance, and accounting [11]. Some Shariah Supervisory Board members who have doctoral backgrounds in economics, finance, and accounting have caused Shariah Supervisory Board Members to not pay too much attention to the presence or absence of earnings management practices in Islamic financial institutions.…”
mentioning
confidence: 99%
“…However, the results of this study indicate that Shariah Supervisory Board meetings have not been effective in knowing and discussing earnings management practices that may be carried out by managers. According to [13] and [3], shariah supervisory boards must be effective in reducing earnings management practices in Islamic banks But, The results of the study of [11] and [14] find evidence that the number of Shariah Supervisory Councils has a negative influence on earnings management practices Based on Table 5.9 shows that the Management Bonus Compensation variable has a significance value of 0.046. This means the Management Bonus Compensation affects Earnings Management.…”
mentioning
confidence: 99%